Evaluation of the 3rd pillar pension funds in Lithuania - Jurevičienė, Daiva; Volkova, Marina (Journal of Business Economics and Management, 2014)
The article emphasizes the increasing importance of the 3rd pillar pension funds and necessity of their assessment in Lithuania. Identified private pension funds evaluation criteria and the expert survey carried out in this paper allowed to ascertain main parameters of evaluation and weigh them according to their importance. Moreover, there is used Delphi method together with Kendall’s coefficient of concordance to assure that the attitude of experts and the results of survey are reconcilable and statistically significant. Finally, created model is tested using funds data analysis to assess its reliability. It is expected that scientific recommendations made based on the analysis of the theoretical studies and empiric research data will assist assessing the 3rd pillar pension funds. In addition, it is supposed that these results will help investors to make a right decision choosing a particular 3rd pillar pension fund and will be a useful tool to encourage investments into private pension funds in the future.